(untitled) (IMC Journal of Medical Science, 2018)
Background and objectives: The magnitude of health problems related to ear, nose and throat (ENT) in Bangladesh has not been estimated in a larger scale and very little is known about the prevalence and types of ENT diseases. Some studies, however, addressed the prevalence of otitis among school children and very few of them reported hearing defect. This study aims to assess the overall types of ENT diseases encountered by the otolaryngologists at a referral or tertiary hospital. Methods: The cross sectional study was conducted in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM). All patients registerd in the ENT-OPD from January to April in 2017 were included in the study for analysis. Diseases were diagnosed on the basis of clinical history, general and systemic examinations and relevant laboratory and imaging investigations. Results: A total of 435 (M :F=177:258) registered patients were analyzed. 44 0f them had no ENT diseases. Diseases of ear showed the highest prevalence (41.1%) followed by that of throat (31.7%) and nose (17.1%). There was no significant difference in ear and nose diseases between male and female groups. The throat diseases were significantly higher in female than the male group (37.2% vs.22.6%, p=0.018). Regarding infections of the specific organs: suppurative otitis media was the most common (acute and chronic suppurative otitis media 25.5%) followed by tonsillitis (7.1%), rhinitis (4.4%) and sinusitis (1.4%). These infections showed no significant difference between male and female patients; neither there was any significant difference between the diabetic and non-diabetic groups. Conclusion: Diseases of ear were most common followed by throat and nose. Both acute and chronic otitis media constituted one-fourth of all registered cases. The diabetic patients showed no increased risk for ENT diseases. IMC J Med Sci 2018; 12(1): 22-26